Mutual cytokine crosstalk between colon cancer cells and microenvironment initiates development of distant metastases - Vaňhara, Petr; Souček, Karel (JAK-STAT, 2013)
Tumor growth and cancer development are considered clear examples of Darwinian selection, whereby random mutational events in heterogeneous cancer cell populations that best fit the selective microenvironment are preferred.(1) As a result, cancer cells evolve resistance to apoptosis, hide from immune surveillance and acquire the ability to invade other organs. Cancer cells, however, are not necessarily passive subjects of selection; they can actively subvert the host tissue to provide a favorable habitat for their growth. Recent findings by Calon et al. convincingly demonstrate that transforming growth factor-β-induced secretion of interleukin 11 by tumor stromal fibroblasts is a necessary prerequisite for the development of distant metastases in colorectal carcinoma. Thus, understanding the complex molecular feedback loops between cancer cells and the surrounding microenvironment (i.e., the tumor-associated stroma or invaded host tissue) should aid the identification of useful molecular targets for improving clinical management of advanced metastatic cancers.
Keywords: interleukin 11; metastasis; tumor stroma; microenvironment; transforming growth factor-β; dissemination; metastatic niche